Analgesic effect of simultaneously targeting multiple pain processing brain circuits in an aged humanized mouse model of chronic pain by transcranial focused ultrasound - Kim, Min Gon; Yeh, Chih-Yu; Yu, Kai; Li, Zherui; Gupta, Kalpna; He, Bin (APL bioengineering, 2025)
Low-intensity transcranial focused ultrasound (tFUS) has recently been shown to noninvasively and non-pharmacologically modulate pain hypersensitivity with high spatial specificity and deep brain penetration. However, the lack of knowledge about its effectiveness for pain management in older subjects vulnerable to severe pain who are also at increased risk of cognitive impairment, presents significant challenges. Additionally, current opioid pain treatments require hospital visits, limiting unwanted serious side effects with multiple liabilities, and device-based pain treatments are typically administered at medical facilities with bulky and expensive equipment, limiting accessibility and thus highlighting the need for at-home non-pharmacological treatment options. Here, we present a more accessible, noninvasive tFUS pain treatment strategy for senior subjects. This approach involves simultaneously targeting multiple pain-processing circuits using a battery-powered, compact, and low-cost ultrasound analog front end (UAFE). We developed and evaluated the performance of the UAFE capable of generating sufficiently high-amplitude output with significantly lower noise levels compared to a commercial transmitter. Using a humanized sickle mouse model of chronic hyperalgesia, we found that tFUS stimulation targeting multiple pain-processing circuits effectively reduces heat hyperalgesia in aged female mice. In addition to its efficacy, our behavioral-based safety assessment revealed no adverse effects on motor functions. These results suggest that using a battery-powered, compact UAFE to simultaneously target multiple pain-processing circuits can effectively suppress heat pain-related behaviors in aged female sickle mice without negatively impacting motor coordination and balance. This highlights the potential for further development of fully home-based tFUS pain treatment for seniors.